IMPROVING SPEAKING ABILITY BY USING PICTURE SERIES - Ana Sri Lestari; Norma Ita Sholichah (LP3M IAI Al-Qolam, 2022)
Speaking ability is a linguistic aptitude or a mode of communication in which a person can communicate his or her thoughts or information in a logical order while mastering the mechanics of speaking convention (pronunciation, grammar, vocabulary, fluency and understanding). The researcher used Picture Series Technique to overcome the challenges that the students were having in this study. This research was conducted in order to improve students’ speaking ability through Picture Series Technique in the first grader students of MTs MUNIR ISMAIL Gondanglegi Malang 2020-2021. The researcher chose Classroom Action Research (CAR) as the technique of research in this study. This study was carried out in two stages by the researcher. The first cycle consisted of two meetings, whereas the second cycle consisted of one meeting. The researcher employed the Picture Series Technique to create a pleasant environment throughout the speaking teaching and learning process, and, more significantly, to increase the students' speaking abilities. The subject of this research was the students of first grader students in MTs MUNIR ISMAIL. The instruments to collect the data were interview, observation checklist, and speaking test. The findings of this study revealed that employing Picture Series Technique in teaching speaking, particularly in describing people, yielded positive results. The researcher might be able to help the pupils enhance their speaking skills. Their comments indicated that they were interested in learning about the subject of speaking since they found it simpler to communicate utilizing the Picture Series Technique. Their average score is 74, based on the results of cycle 1. As a consequence of the second cycle, their average score is 81.